Berry & Kohn's operating room technique - Phillips, Nancymarie Fortunato (St. Louis, Missouri : Elsevier, 2017)
"This is a nursing textbook about operating room technique"--
Includes bibliographical references and index.
Keywords: Operating room nursing; Perioperative care - methods